Complement-Opsonized HIV Modulates Pathways Involved in Infection of Cervical Mucosal Tissues: A Transcriptomic and Proteomic Study - Svanberg, Cecilia; Ellegård, Rada; Crisci, Elisa; Khalid, Mohammad; Borendal Wodlin, Ninnie; Svenvik, Maria; Nyström, Sofia; Birse, Kenzie; Burgener, Adam; Shankar, Esaki M.; Larsson, Marie (Frontiers in Immunology, 2021)
Genital mucosal transmission is the most common route of HIV spread. The initial responses triggered at the site of viral entry are reportedly affected by host factors, especially complement components present at the site, and this will have profound consequences on the outcome and pathogenesis of HIV infection. We studied the initial events associated with host-pathogen interactions by exposing cervical biopsies to free or complement-opsonized HIV. Opsonization resulted in higher rates of HIV acquisition/infection in mucosal tissues and emigrating dendritic cells. Transcriptomic and proteomic data showed a significantly higher expression of genes and proteins associated with viral replication and pathways involved in different aspects of viral infection. This clearly suggests that HIV opsonization alters the signaling pathways in the cervical mucosa in a manner that promotes viral establishment and infection. Our findings provide a foundation for further studies of the role these early HIV induced events play in HIV pathogenesis.